Analyse linguistique d’un discours sur un événement en cours: le cas du 11 septembre 2001 - Danino, Charlotte (Neophilologica, 2014)
The linguistic dimension of events is often considered from the point of view of subsequent discourses in the written media. From its first moments however, the event prompts spontaneous aural verbal reactions, which we can access thanks to audiovisual media. These almost concomitant linguistic productions are the target of our study, here using the example of September 11, 2001, which happened live on most channels, including CNN which provided us with our corpus. The core issue is that of meaning construction mechanisms, specifically, the issue of constructing a discourse when a stabilized meaning (of what is happening) is unavailable: how do we talk about something when we are not sure what we are talking about? How do we ground discourse and determine access to information between perception and expression, description and interpretation? These questions raise a number of methodological issues, which this presentation aims to account for. The proposed solutions will try to prove the relevance of cognitive semantics and more specifically that of instructional semantics (Col et al., 2012).